Communication and environment sustainability and risks - Hamidah, Abd Hamid; Azman, Azwan Azmawati; Jamilah, Hj Ahmad; Nik Norma, Nik Hasan (Proceedings series / Penerbit USM)
There is a dearth of literature on environmental communication within the non-western world. The few existing ones are scattered and not easily available. Thus, there is a dire need to document research and literature in the field. The opportunity arose at the 2009 International Conference on Communication and Environment held in Penang, Malaysia. The international conference with the theme "Transformation for a Sustainable Tomorrow", organised by the School of Communication, Universiti Sains Malaysia (USM), attracted scholars, practitioners and activists from around the world to listen and deliberate on various aspects of communication and environment. The post-conference review resulted in the selection of 24 papers to be compiled into this edited volume.